2018
DOI: 10.2334/josnusd.16-0827
|View full text |Cite
|
Sign up to set email alerts
|

Biological evaluation of subgingivally placed direct resin composite materials

Abstract: In addition, high-performance liquid chromatography (HPLC) was used to determine release of resin monomers from RBCs after 1 h, 1 day, and 7 days. As compared with tissue culture plastics (the control), cellular adhesion was significantly lower (P < 0.001) for human gingival fibroblasts and osteoblasts. Only minor, nonsignificant differences between individual RBCs were identified. HPLC analyses identified the release of three bifunctional methacrylates bisphenol A glycerolate dimethacrylate, triethylene glyco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…15 Biocompatibility and cytotoxicity are another important concern because of the elution of cytotoxic substances like unreacted monomers in dental resin composites that can be harmful to tissues around the restoration, thus inducing systematic responses. 16,17 Besides the mentioned factors, other criteria such as polymerization shrinkage, secondary caries, and marginal fractures are other material-related drawbacks of dental resin composites. 18 The clinical performance of dental restoration and its overall success is the result of all criteria mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…15 Biocompatibility and cytotoxicity are another important concern because of the elution of cytotoxic substances like unreacted monomers in dental resin composites that can be harmful to tissues around the restoration, thus inducing systematic responses. 16,17 Besides the mentioned factors, other criteria such as polymerization shrinkage, secondary caries, and marginal fractures are other material-related drawbacks of dental resin composites. 18 The clinical performance of dental restoration and its overall success is the result of all criteria mentioned above.…”
Section: Introductionmentioning
confidence: 99%
“…High Performance Liquid Chromatography (HPLC) analysis identified release of bisphenol A glycerolate dimethacrylate, TEGDMA and diurethane dimethacrylate from composite resins (Tetric Evo Ceram, Tetric Ceram, Dyract Xtra, Filtek Supreme XTE, Admira) and shown that monomers release increases between 1 hour and 1 day but remains low (Frese et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…53 Similarly, the development of novel antimicrobial biomaterials promises benefits for DME once the challenges of biocompatibility and controlled release of antimicrobial agents are overcome. 54,55 Furthermore, following case reports demonstrating favorable outcomes of a novel technique, a clinical trial is investigating the performance of RBC restorations placed on calcium-silicate cement applied in marginal defects extending to the alveolar crest. 56 Currently available data do not provide conclusive evidence on which adhesive strategy is most appropriate for DME.…”
Section: Sequence Of Restorative Procedures In In Vitro/in Silico Stu...mentioning
confidence: 99%